Economic and Social Determinants of Corn Farmers' Consumption Patterns: A Survey and Regression Analysis Approach - Hartanto, Wiwin; Mu’alimah, Silvi; Sukarniati, Lestari (JAMPE (Journal of Asset Management and Public Economy), 2024)
This research discusses the consumption patterns of corn farming households in Indonesia which are influenced by economic and social factors. This study aims to examine consumption expenditure based on income, number of family members, education, age, and differences in place of residence. The research method used was quantitative with multiple linear regression statistical analysis, using primary data from 86 corn farming households. The research results show that income is the biggest factor influencing household consumption of corn farmers. Factors such as income, number of family members and education of the head of the family have a positive and significant effect on consumption patterns. Although age does not have a significant effect, this research provides important insights into the consumption behaviour of corn farmers in Indonesia, including the importance of wise consumption expenditure management to improve the welfare of farming households. These findings show that income, education, and family size play a key role in shaping consumption habits. This study also highlights how economic factors influence people's consumption patterns in various communities, both farmers and urban residents, and the importance of understanding these factors in planning policies that support the welfare of society as a whole. The contribution of this research is expected to bridge the results of previous studies with policy development, emphasizing the need for targeted programs considering income, family size, education, and residence location to improve the welfare of corn farming households in Indonesia.